Informed Consent: The Rate-Limiting Step in Acute Stroke Trials - Rose, David Z.; Kasner, Scott E. (Frontiers in Neurology, 2011)
Successful implementation of a randomized clinical trial (RCT) for neuro-vascular emergencies such as cerebral infarction, intracerebral hemorrhage (ICH), or subarachnoid hemorrhage (SAH) is difficult. Besides establishing an accurate, hyper-expedited diagnosis among many mimics in a person with acute neurological deficits, informed consent must be obtained from this vulnerable group of patients who may be unable to convey their own wishes, grasp the gravity of their situation, or give a complete history or examination. We review the influences, barriers, and factors investigators encounter when providing established and putative stroke therapies, and focus on informed consent, the most important research protector of human subjects, as the rate-limiting step for enrollment into acute stroke RCTs. The informed consent process has received relatively little attention in the stroke literature, but is especially important for stroke victims with acute cognitive, aural, lingual, motor, or visual impairments. Consent by a surrogate may not accurately reflect the patient’s wishes. Further, confusion about trial methodology, negative opinions of placebo-controlled studies, and therapeutic misconception by patients or surrogates may impede trial enrollment and requires further study. Exception From Informed Consent (EFIC) offers an opportunity that is rarely if ever utilized for stroke RCTs. Ultimately, advancing the knowledge base and treatment paradigms for acute stroke is essential but autonomy, beneficence (non-malfeasance), and justice must also be carefully interwoven into any well-designed RCT.